Hybrid HMSIW Cavities Antenna With a Half-Pentagon Ring Slot for Bandwidth Enhancement - Dian Widi Astuti; Yuyu Wahyu; Fitri Yuli Zulkifli; Eko Tjipto Rahardjo (IEEE Access, 2023)
A substrate-integrated waveguide (SIW) antenna is an implementation of a waveguide antenna in a microstrip antenna. The microstrip antenna, as a low-profile antenna, suffers from narrow impedance bandwidth. This paper proposes a novel bandwidth enhancement method for solving a narrow impedance bandwidth. Bandwidth enhancement was achieved by using quad-resonant frequencies. The quad-resonant frequencies are resulted from the hybrid half-mode substrate-integrated waveguide (HMSIW) cavities between the inner and outer cavities. The inner HMSIW cavity has a half-pentagon ring slot that disturbs the TE $_{101-inner}$ , TE $_{102-inner}$ , TE $_{202-inner}$ , and TE $_{103-inner}$ modes, whereas the outer HMSIW cavity consists of two outer quarter-mode substrate-integrated waveguide (QMSIW) cavities. The outer HMSIW cavity generated the TE $_{102-outer}$ and TE $_{202-outer}$ modes. The hybrid cavities were fed simultaneously using a port with a quarter-wavelength feed transmission line. The hybrid HMSIW cavities generated resonant frequencies that were close to each other. Additionally, this method was applied to the X-band frequency with a low-profile substrate. The simulated impedance bandwidth and peak realized gain was 33.86% ( $8.98-12.64$ GHz) and 7.97 dBi, while the measured impedance bandwidth and peak gain were 31.83% (9.14 – 12.6 GHz) and 7.62 dBi, respectively. Strong agreement was observed between the measurement and simulation results.